"Indian foreign policy in Cambodia, Laos and Vietnam 1947 - 1964" - "SarDesai, D.R." (Berkeley, 1968)
This book deals with Indian Foreign Policy with reference to Cambodia, Laos and Vietnam during 1947-1964.
Keywords: India - Foreign relations Cambodia